Evaluation of the presence of HLB in Rutaceae in nature reserves in Misiones, Argentina - Gochez, Alberto Martín; Aranda, M. Paula; Velozo, Lucía; Buemo, Carla; Rodríguez, Manuela; Agostini, Juan Pedro; Talavera, Liliana; Alayon Luaces, Paula; Gaiad, Emilio; Argüelles, Carina F.; Miretti, Marcos (2017)
The disease Huanglongbing (HLB) is currently the most serious threat for Argentina’s Citrus industry. Early diagnosis of affected tissues requires conventional molecular methods, polymerase chain reaction (PCR) or quantitative real time PCR (qPCR), due to the inability to grow any of the bacteria involved in the disease etiology: Candidatus Liberibacter asiaticus (CLas), africanus (CLaf), and americanus (CLam). Because HLB is incipient in Argentina eradication of all infected plants is recommended, however the presence of HLB in wild plants cannot be ruled out or has not been locally studied.